2020
DOI: 10.1177/1040638719900180
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium perfringens type C necrotic enteritis in pigs: diagnosis, pathogenesis, and prevention

Abstract: Clostridium perfringens type C causes severe and lethal necrotic enteritis (NE) in newborn piglets. NE is diagnosed through a combination of pathology and bacteriologic investigations. The hallmark lesion of NE is deep, segmental mucosal necrosis with marked hemorrhage of the small intestine. C. perfringens can be isolated from intestinal samples in acute cases but it is more challenging to identify pathogenic strains in subacute-to-chronic cases. Toxinotyping or genotyping is required to differentiate C. perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 67 publications
2
26
0
Order By: Relevance
“…Targeting this membrane molecule makes sense for pathogens like C. perfringens type C, which profit from a disturbed tissue perfusion at the site of infection. The targeting of endothelial cells via this specific CPB-CD31 interaction fits to the early vascular damage we described in an intestinal porcine infection model (Schumacher et al, 2013) and the massive intestinal hemorrhage observed in spontaneous C. perfringens type C enteritis (Posthaus et al, 2020). In our study, we confirmed the in vivo role of CD31 using a mouse toxemia model.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Targeting this membrane molecule makes sense for pathogens like C. perfringens type C, which profit from a disturbed tissue perfusion at the site of infection. The targeting of endothelial cells via this specific CPB-CD31 interaction fits to the early vascular damage we described in an intestinal porcine infection model (Schumacher et al, 2013) and the massive intestinal hemorrhage observed in spontaneous C. perfringens type C enteritis (Posthaus et al, 2020). In our study, we confirmed the in vivo role of CD31 using a mouse toxemia model.…”
Section: Discussionsupporting
confidence: 87%
“…This model does not reflect the intestinal pathology induced in the natural disease. However, it can be used to determine the systemic effects of CPB toxemia, which have been suggested to occur also in the natural disease (Posthaus et al, 2020). We could clearly show that CD31-deficient mice are protected against the systemic and lethal effects of CPB.…”
Section: Discussionmentioning
confidence: 73%
“…Symptoms of its infection in piglets include severe diarrhoea, accompanied by necrotic mucosa and intestinal villi atrophy [7,8]. Currently, C. perfringens infections has become an important problem hindering the development of the pig industry [9,10]. Probiotics are de ned as "live microorganisms that, when administered in adequate amounts, confer a health bene t on the host" [11].…”
Section: Introductionmentioning
confidence: 99%
“…Similar lesions are frequently observed in foals and calves naturally diseased with type C strains [ 208 , 210 , 216 ]. CPB inhibition of platelet function may be responsible for systemic hemorrhages [ 291 ].…”
Section: Molecular Pathogenesis Of C Perfringens mentioning
confidence: 99%